GR/Sp3/HDAC1/UGDH signaling participated in the maternal dexamethasone‐induced dysplasia of the rat fetal growth plate. Issue 9 (7th August 2020) - Wen, Yinxian; Shi, Huasong; Wu, Zhixin; Xiao, Hao; Wang, Hui; Chen, Liaobin
Abstract: Maternal dexamethasone decreases the body length of the newborn. However, whether dexamethasone inhibits the development of the growth plate of the fetal long bone is still unknown. Here, we found that lengths of fetal femur and growth plate were both shorter in the fetuses with maternal dexamethasone (0.2 mg/kg.d from gestation day 9 to 20), with a decreased proteoglycan content of the growth plate in the fetal rat. Notable decreases in both the gene expression and H3K9 acetylation of UDP‐glucose dehydrogenase ( Ugdh ) gene, which codes a key enzyme in the proteoglycan biosynthesis in the chondrocyte, were also observed. Meanwhile, up‐regulation of glucocorticoid receptor ( GR ), specific protein 3 ( Sp3 ), and histone deacetylase 1 ( Hdac1 ) gene expression were detected in the fetal growth plate. Similar changes were also observed in the chondrogenic rat bone marrow stromal cells (BMSCs) with excessive exogenous dexamethasone. However, antagonizing GR with RU486 and silencing Hdac1 or Sp3 with specific siRNAs could all stimulate the H3K9 acetylation and gene expression of Ugdh previously inhibited by dexamethasone. Meanwhile, dexamethasone also induced the nuclear translocation of GR, which further directly bound to the Ugdh promoter and interacted with HDAC1 and Sp3, respectively. Collectively, our study revealed that maternal dexamethasone induced the direct binding of GR to the Ugdh promoter of the chondrocyte in the rat fetal growth plate, which recruited HDAC1 and Sp3, induced deacetylation of the H3K9, and subsequently inhibited Ugdh gene expression. Such changes further led to attenuated proteoglycan synthesis in the developing chondrocyte and therefore disrupted the development of growth plate and fetal long bone.